Creative writing - Nery, Solis Peter (Makati City : Diwa Learning Systems, Inc., 2020)
"This textbook second edition's most charming appeal is its generosity of spirit, its youthful appeal, and spot-on understanding of the third-millennium gadget-obsessed, cyber-savvy, novice Filipino writer who wants to explore, understand, and pursue the literary life. Penned by one of the most awarded under-50 Filipino writers today, who straddles across the various genres--fiction, drama, poetry, and even film--with honors to boot, this module is a distillation of ideas, theories, and best practices that have worked in many creative writing lecture-workshops and literature seminars conducted over the years".
Includes bibliography.
English text.
Keywords: Creative writing